Synthesis and Optical Properties of Imidazole‐Based Fluorophores having High Quantum Yields. Issue 3 (27th January 2014) - Lessi, Marco; Manzini, Chiara; Minei, Pierpaolo; Perego, Luca A.; Bloino, Julien; Egidi, Franco; Barone, Vincenzo; Pucci, Andrea; Bellina, Fabio
Abstract A series of 1, 4‐phenylene‐spaced bis‐imidazoles with fluorescence quantum yields up to 0.90 and large Stokes shifts have been designed and synthesized using recently developed regioselective direct CH arylation protocols. All the fluorophores show a bright blue‐green emission that is well retained in the solid state. DFT calculations attributed their excellent luminescence properties to the significant planarization of the molecules in the equilibrium structures of their excited electronic states.